Assessing Indoor Dust Interference with Human Nuclear Hormone Receptors in Cell-Based Luciferase Reporter Assays - Young, Anna S. (Environ Health Perspect, 2021)
BACKGROUND: Per- and polyfluoroalkyl substances (PFAS), organophosphate esters (OPEs), and polybrominated diphenyl ethers (PBDEs) are hormone-disrupting chemicals that migrate from building materials into air and dust. OBJECTIVES: We aimed to quantify the hormonal activities of 46 dust samples and identify chemicals driving the observed activities. METHODS: We evaluated associations between hormonal activities of extracted dust in five cell-based luciferase reporter assays and dust concentrations of 42 measured PFAS, OPEs, and PBDEs, transformed as either raw or potency-weighted concentrations based on Tox21 high-throughput screening data. RESULTS: All dust samples were hormonally active, showing antagonistic activity toward peroxisome proliferator-activated receptor ([Formula: see text]) (100%; 46 of 46 samples), thyroid hormone receptor ([Formula: see text]) (89%; 41 samples), and androgen receptor (AR) (87%; 40 samples); agonist activity on estrogen receptor ([Formula: see text]) (96%; 44 samples); and binding competition with thyroxine ([Formula: see text]) on serum transporter transthyretin (TTR) (98%; 45 samples). Effects were observed with as little as [Formula: see text] of extracted dust. In regression models for each chemical class, interquartile range increases in potency-weighted or unknown-potency chemical concentrations were associated with higher hormonal activities of dust extracts (potency-weighted: [Formula: see text] , [Formula: see text] , [Formula: see text]; [Formula: see text] , [Formula: see text] , [Formula: see text]; [Formula: see text] , [Formula: see text] , [Formula: see text]; [Formula: see text] , [Formula: see text] , [Formula: see text]; unknown-potency: [Formula: see text] , [Formula: see text] , [Formula: see text]; [Formula: see text] , [Formula: see text] , [Formula: see text]), adjusted for chemicals with active, inactive, and unknown Tox21 designations. DISCUSSION: All indoor dust samples exhibited hormonal activities, which were associated with PFAS, PBDE, and OPE levels. Reporter gene cell-based assays are relatively inexpensive, health-relevant evaluations of toxic loads of chemical mixtures that building occupants are exposed to. https://doi.org/10.1289/EHP8054